Pengaruh Lingkungan Kerja terhadap Kinerja Tenaga Pendidik di Madratsah Aliyah Negeri Pekanbaru - Nashikhah, Durotun; Mahnun, Nunu (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
This research is a regression research consisting of variable X (Work Environment) and variable Y (Performance of Educators). This research aims to determine the influence of the work environment on the performance of teaching staff in State Madrasah Aliyah throughout Pekanbaru City. The subjects in this research are State Madrasah Aliyah Educators, the research object is the Influence of the Work Environment on Performance. The population used in this research was 213 teaching staff. The sample was taken randomly as many as 69 teachers. The data collection technique in this research uses a questionnaire in the form of a questionnaire, then the data is analyzed using descriptive percentages and simple linear regression. Based on the research results, it shows that there is a significant influence of the work environment on the performance of teaching staff with a t value of 3.897, greater than t table of 1.997. So the better the work environment, the better the performance of the State Madrasah Aliyah teaching staff throughout Pekanbaru City. Therefore, the work environment must be managed well, so that good management will create the expected performance.